From relational art to the search for new formes of life: arts teaching in basic education in the context of social vulnerability (Revista NUPEART, 2023)
The present article is based on the assumption that school is a mechanism of subjugation of young people in social vulnerability, whose constituent elements work to generate cultural indigence, materialized in school exclusion. It turn to Relational Art and later the decolonial thinking as poetics and pedagogical practices that can mitigate the context of violence and exclusion or even subvert the functioning of the school space. The conclusion attests that relational art practices function in a way that propitiates the maintenance of the political-social system, not generating deep transformations at the context. While decolonial practices can provide experiences of community that are not restricted to a temporal lapse, but cross time and generations, creating affective acts, identity, and political, that empower bodies and agency struggles, occasioning and being the results of structural changes.
Keywords: education; social vulnerability; relational art; decolonial thinking